Design of High Performance Distributed Snapshot / Recovery Algorithms for Ring Networks - Gupta, Bidyut; Rahimi, Shahram; Liu, Ziping (Journal of computing and information technology, 2008)
In this work, we have presented non-blocking checkpointing and recovery algorithms for bidirectional networks. We have deviated from the conventional approach of taking first temporary checkpoints and then converting them to permanent ones by processes (as followed by any coordinated checkpointing scheme). Thus, the proposed coordinated checkpointing algorithm allows processes to take permanent checkpoints directly without taking temporary checkpoints and whenever a process is busy, it takes a checkpoint after completing its current procedure. We have shown that the presented algorithms take much less time for their execution and use much less number of control messages (and hence much less number of interrupts to a process) when compared to a noted recent work [4].